Pertanggungjawaban Pidana Tenaga Medis Yang Melakukan Pengguguran Kandungan - Alfaresi, Muhammad Bima; Abdullah, Muhmmad Zen; Sarbaini, Sarbaini (Legalitas: Jurnal Hukum, 2024)
Medical personnel have a code of ethics in carrying out their duties in providing health services to patients. However, it is found that medical personnel perform abortion, then this fulfils the elements of a criminal offence and is accountable as stipulated in the Criminal Code (KUHP) prohibiting abortion without exception, then the Law of the Republic of Indonesia Number 36 Year 2009. Therefore, this article aims to analyse the Criminal Liability of Medical Personnel Who Perform Obstetric Miscarriages